Ethical considerations referred to in child health research published in leading nursing journals: 2015–2019. Issue 3 (14th September 2020) - Wu, Yanni; Howarth, Michelle; Zhou, Chunlan; Yang, Lixiao; Ye, Xiaoling; Wang, Run; Li, Chaixiu; Hu, Mingyu; Cong, Weilian
Abstract: Background: Child health research comprises complex ethical considerations. Understanding the extent to which the ethical process is reported in child health research is needed to improve reporting. Aims: To identify reportage of ethical considerations in child health research in leading nursing and paediatric journals. Methods: All child health research published between 2015 and 2019 in 10 leading nursing journals and two paediatric journals were retrieved and critically appraised for the reportage of informed consent and ethical approval. Results: Eight hundred and fifty‐one child health research papers were included. Although 544 (79.9%) of the prospective studies mentioned informed consent, only 300 (55.2%) reported that written informed consent was obtained from the participants. Overall, 748 (87.9%) of child health research papers noted obtaining research ethics committee approval. Articles that mentioned financial support were significantly more likely to report informed consent and ethical approval than unfunded studies (all P < 0.001). Prospective studies showed higher rates of reportage of ethical approval compared to retrospective studies ( P = 0.027). Rates of child consent (assent) obtained in different age groups of children ranged from 29.6% to 66.3%. Conclusion: Despite improvements in the reportage of ethical review and approval processes in child health research, consistent and transparent reports are still lacking. SUMMARY STATEMENT: What is already known about this topic? Research related to child health has highlighted concerns about ethical and methodological considerations. Little work has systematically assessed the reportage of ethical considerations in child health research. What this paper adds? To our knowledge, this is the first study to investigate the ethical considerations in child health research published in recent years. The research explored how ethical protections are performed and reported in child health research and identified that efforts from publishers and researchers still needed. The implications of this paper: Strategies are still required to ensure the rights of children are upheld in medical research The significant ethical issues that attend engaging children in research and protecting their rights is, and must remain, priorities of medical researchers.